2022
DOI: 10.3390/cancers14082047
|View full text |Cite
|
Sign up to set email alerts
|

Novel Intraoperative Navigation Using Ultra-High-Resolution CT in Robot-Assisted Partial Nephrectomy

Abstract: To assess the perioperative and short-term functional outcomes of robot-assisted partial nephrectomy (RAPN) with intraoperative navigation using an ultra-high-resolution computed tomography (UHR-CT) scanner, we retrospectively analyzed 323 patients who underwent RAPN using an UHR-CT or area-detector CT (ADCT). Perioperative outcomes and the postoperative preservation ratio of estimated glomerular filtration rate (eGFR) were compared. After the propensity score matching, we evaluated 99 patients in each group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…One of the most popular is percutaneous cryoablation (PCA) [ 35 ], which is surrounded by controversies in the literature. While some studies suggest that RAPN and PCA have similar oncological outcomes in patients with small renal masses [ 36 ], others report that the recurrence rate is significantly higher after PCA vs RAPN [ 37 ], so it is essential to individualize the technique according to each patient and their neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most popular is percutaneous cryoablation (PCA) [ 35 ], which is surrounded by controversies in the literature. While some studies suggest that RAPN and PCA have similar oncological outcomes in patients with small renal masses [ 36 ], others report that the recurrence rate is significantly higher after PCA vs RAPN [ 37 ], so it is essential to individualize the technique according to each patient and their neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Takahara et al emphasized that success during RAPN depends on obtaining accurate information about the anatomical relationships between the tumor and the urinary vascular structures surrounding it and the precision of the 3DVR images used. 46 They used an ultra-high-resolution CT scanner to obtain 3DVR images for intraoperative navigation and compared it with conventional CT. The use of the ultra-highresolution CT scanner resulted in superior surgical outcomes in terms of the warm ischemic time and estimated intraoperative blood loss.…”
Section: Navigation During Rapnmentioning
confidence: 99%
“…Dynamic contrast-enhanced CT of the kidney accurately confirms the anatomical relationship between the tumors, surrounding vascular structures, and the urinary tract through intravascular contrast enhancement of the arterial, venous, and excretion phases. We have previously reported a novel navigation system using an ultrahigh-resolution CT scanner that provides a shorter WIT and lower estimated blood loss (EBL) than areadetector CT. We concluded that this novel navigation system could be useful in patients undergoing RAPN [6]. Before RAPN surgery, 3D constructions of the renal tumor, vascular structures, and the urinary tract were performed using various image processing software based on these CT imaging data.…”
mentioning
confidence: 99%